Optimizing Public-Private Partnerships for Improved Efficiency and Sustainability of Public Infrastructure in Indonesia - Muhsin, Isna; Nugraha, R. Eka; Nurdin, Ismail (STIE Amkop Makassar, Indonesia, 2025)
Public Private Partnership (PPP) has become a strategic solution in overcoming the challenges of limited government budget for infrastructure development and public service improvement. This study aims to analyze the implementation of PPP in Indonesia, including risk sharing, operational efficiency, technological innovation, and social and sustainability impacts. Using a descriptive qualitative approach, data was collected through literature review, semi-structured interviews, and document analysis. The results show that the success of PPPs is determined by equitable risk sharing between the government and the private sector, operational efficiency through technology adoption, and transparent and accountable oversight. However, challenges such as unequal risk sharing, limited institutional capacity, and conflict of interest require serious attention. This research recommends flexible contract design, institutional strengthening, and inclusive tariff policies to ensure sustainability and positive social impacts. With a holistic approach, PPP has the potential to support sustainable development in Indonesia through synergy between the public and private sectors.